Hubungan ASI Eksklusif dengan Kejadian Underweight di Jawa Timur Tahun 2016 - Mahmudah Wati Sugito; Agus Sri Wardoyo; Trias Mahmudiono (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2017)
Background: Underweight is a public health problem caused by many factors. The prevalence of underweight in East Java in 2016 was 17.3%, wich was higher than the program’s targetted (12.9%). Breast milk is the best food to support the growth and development of the baby. Coverage of Exclusive Breast Milk in East Java in 2015 decreased (68.8%), compared to 2014 (72.89%). Early supplementary feeding in infants under 6 months may affect nutritional status. Objectives: The purpose of this study was to analyze the relationship of Exclusive Breast milk with the incidence of underweight in infants aged 0-23 months in East Java Province in 2016. Method: This study is a secondary data analysis of Nutrition Status Monitoring in East Java Province. The study population was all babies in East Java. Total sample is 4738. The data were analyzed using Chi-square test and Logistic Regression, with 95% CI (α = 0.05). Results: The results showed there was a significant relationship between exclusive breastfeeding only from birth until before the last 24 hours in infants aged 0-23 months with the incidence of underweight, with (p=0.000010;OR=1.654;95%CI=1.319–2.052), there was a significant relationship of first to provide a food other than breast milk in infants aged 0-23 months with the occurrence of underweight, (p = 0.000;OR=0.272; 95%CI=0.217–0.341).Conclusion: In conclusion, breastfeeding only in infants from birth until before the last 24 hours and first provide food other than breast milk in infants aged 0-23 months associated with underweight. Because breast milk is sufficient nutritional needs of infants aged 0-6 months.ABSTRAK Latar Belakang: Masalah gizi kurang merupakan masalah kesehatan masyarakat yang disebabkan oleh banyak faktor. Prevalensi underweight di Jawa Timur tahun 2016 sebesar 17,3%, lebih tinggi dari target program Dinas Kesehatan Provinsi Jawa Timur sebesar 12,9%. ASI merupakan makanan terbaik untuk mendukung pertumbuhan dan perkembangan bayi. Cakupan ASI Eksklusif di Jawa Timur tahun 2015 menurun (68,8%), dibandingkan tahun 2014 (72,89%). Pemberian makanan pendamping ASI dini pada bayi di bawah 6 bulan dapat mempengaruhi status gizi. Tajuan: Tujuan penelitian untuk menganalisis hubungan ASI Ekslusif dengan kejadian underweight pada bayi usia 0-23 bulan di Provinsi Jawa Timur tahun 2016.Metode: Penelitian ini merupakan analisis data sekunder survei Pemantauan Status Gizi Provinsi Jawa Timur. Populasi penelitian adalah semua bayi berusia 0-59 bulan yang ada di Jawa Timur. Total sampel sebanyak 4738 bayi. Analisis data dilakukan dengan menggunakan uji Chi-square dan Regresi Logistik.Hasil: Hasil penelitian menunjukkan ada hubungan antara pemberian ASI saja sejak lahir sampai sebelum 24 jam terakhir pada bayi usia 0-23 bulan dengan kejadian underweight (p=0,000010;OR=1,654;95%CI=1,319–2,052), ada hubungan pertama kali memberikan makanan selain ASI pada bayi usia 0-23 bulan dengan kejadian underweight, (p = 0,000;OR=0,272; 95%CI=0,217–0,341).Kesimpulan: Simpulan yaitu pemberian ASI saja pada bayi sejak lahir sampai sebelum 24 jam terakhir dan pertama kali memberikan makanan selain ASI pada bayi usia 0-23 bulan berhubungan dengan kejadian underweight. Pemberian ASI saja sudah mencukupi kebutuhan nutrisi bayi usia 0-6 bulan.